THE EFFECT OF USING CONTEXT CLUES STRATEGY ON READING COMPREHENSION AT THE FIRST GRADE STUDENTS OF SMK HARAPAN BANGSA PANTI - Khairani, Nikmah (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
THE MAIN PROBLEM OF THIS RESEARCH WAS “IS THERE ANY SIGNIFICANT EFFECT OF USING CONTEXT CLUES STRATEGY TOWARD STUDENTS’ READING COMPREHENSION?”. Therefore, objective of this research was to find out whether or not there is significant effect of using context clues strategy on students’ reading comprehension. In this research, the researcher used quasi- experimental method by using the pre-test and post-test. The population of this research was 142 students consisting of four classes. The sample was X.OTKP there are 34 students which was treated as experimental class taught by using context clues strategy and X.BDP there are 34 students which was treated by conventional. Based on the finding, three hypothesis (Ha) were accepted. The first, the result of the pre-test and the post-test scores of experimental class was found that the tobtained (10,31) more than ttable (1,960). The second, the result of the post-test scores of experimental and control class were found that the tobtained (4,21) more than the ttable( 1,960). The last, the result of the post-test of experimental class and control class were found that tobtained (4,21) more than ttable (1,960). It means that by using context clues strategy in teaching English gives significant effect on students’ reading comprehension.